Asking Questions About Mature Artistry and Adaptive Practices in Canadian Dance - El-Ghazouly, Yomna; Lee, Heunjung; Barnstaple, Rebecca; J. Kenny, Sarah; Hansen, Pil (Cena, 2026)
Aging in professional dance deserves reframing; Rather than tropes of decline, the (re)generative modes of artistic inquiry that mature dancers develop can inform perceptions of aging. We examined over a hundred publications spanning dance studies, dance science, and dance education, and learned that mature dancers embody adaptive intelligence through strategies of improvisation and redistribution and practices centered on mindfulness, expression, and spirituality. Yet, the strengths and expertise of mature dancers remain under-recognized due to pervasive ageism within Western dance cultures. Our cross-disciplinary literature review reveals a lack of integrated insight into mature dancers’ artistry and health-related knowledge, including challenges, strengths, and potential forms of support. We propose a participatory, transdisciplinary framework for studying aging in dance that transcends boundaries between artistic and scientific knowledge, positioning mature dancers as co-producers of questions, methods, interpretation of evidence, and application of discoveries to practice. Our proposal is arrived at in two steps: First, we integrate existing findings on mature artistry and health across disciplines, which leads us to advocate for a transdisciplinary epistemology that enables clinical metrics to be considered alongside artistic analysis and positions mature artistry as a system of adaptive intelligence. Second, we connect insights from studies of community-based dance for older adults as inspiration to develop a participatory, transdisciplinary research framework. This framework centers mature dancers’ embodied knowledge and modes of inquiry in the design, interpretation, and dissemination of research. By treating aging as a choreography of adaptation, the proposed framework transforms how expertise is recognized and how movement itself becomes a site of knowledge production.